DECISION SUPPORT SYSTEM FOR SELECTING HOUSING AREAS USING ELECTRE METHOD - Eri Eriana; Ivan Pilhanudin; Raffi Maulana; Muhamad Edgar; Riki Ridwan Margana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
CV. PondokMulyaMelati Wangi is a company that works on construction projects from planning to implementation. The planning includes making work drawings, 3-dimensional drawings, site plans, RAB (Budget Design), structural design, and IMB management. Meanwhile, the implementation of the company includes new building works, renovations, making floors, fences, terraces, stairs, replacing tiles, ceilings, repainting, manufacturing and installing door frames, aluminum, etc. The decision support system for selecting the location of a residential area aims to make it easier for owners or companies to choose the newest location options in creating a residential area. The decision support system for selecting the location of a residential area uses the method ELECTRE (Elimination Et Choix Traduisant la Realite. The benefit of doing this research is to get the opportunity to further explore and expand knowledge about the use of the method ELECTRE (Elimination Et Choix Traduisant la Realite) and on decision support systems. Researchers draw conclusions to answer the research objectives. One of them is to know the working steps of the methodELECTRE in designing a decision support system that must be done. By using the ELECTRE method, the researcher makes it easier to determine alternatives based on the weight of the assessment and predetermined criteria, thus facilitating the process of making valid decisions and being able to determine the location of residential areas more quickly and accurately. In this study, tests will also be carried out to prove that the ELECTRE method can be used to determine the location of the best residential area from several alternatives and predetermined criteria.